Membranes for Water and Wastewater Treatment - Hidalgo, Asuncion Maria; Murcia, Maria Dolores (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Water is a vital element for life and the environment. Water pollution has been documented as a contributor to a wide range of health problems. In recent years, the water quality levels have suffered great deterioration because of rapid social and economic development and because it is used to "dump" a wide range of pollutants.This book entitled "Membranes for Water and Wastewater Treatment" contains featured research papers dealing with recent developments and advances in all aspects related to membranes for water and wastewater treatment: membrane processes, combined processes (including one membrane step), modified membranes, new materials, and the possibility to reduce fouling and to improve the efficiency of enhanced processes. The papers compiled in this Special Issue can be read as a response to the current needs and challenges in membrane development for water and wastewater treatment.Half of the research articles correspond to concrete and practical applications of the use of membrane processes in different fields of the industry, with the aim of treating and conditioning water and wastewater. The studies reveal the treatment of industrial streams, mining, recycled paper industry, olive mill, urban wastewater, etc. Another important percentage of studies are related to membrane modification processes, with the aim of obtaining new materials with better performance in the separation processes, thus describing the use of membranes modified with chitosan, nanoparticles, and other organic compounds. This field also includes studies related to fouling and its modeling.